The Effect of Monosodium L-Glutamate (MSG) Treatment for Short and Long Terms to The Semen Quality of Adult Male Rats - Anzila, Ivakhul; Warih Marhendra, Agung Pramana; Rahayu, Sri (The Journal of Experimental Life Science, 2019)
This study was conducted to investigate the effect of MSG treatment for short and long term on the semen quality of adult male rats. Twelve male adult Wistar rats with 200-300g of body weight (BW) and 3-4 month of age were used in this study. The animals were divided randomly into 3 groups. M0 was used as a control, M1 and M2 were given with MSG 4mg/gBW for 15 andÂ 45 days respectively. The experimental animals were sacrificed on the days 16th (to M1 group) and 46th (to M0 and M2 groups). The epididymis was isolated and semen quality (motility, viability, concentration, and abnormality of sperm) was evaluated. The results showed motility and concentration of M1 and M2 were not significantly decreased compared to M0. MSG treatment also significantly reduced viability and increased abnormality of sperm. Analysis of sperm abnormality character shows that the use of long-term MSG caused a formation of the primary abnormality (round and double head sperm) and increased the secondary abnormality (bent neck, curve tail, coiled tail, headless, and tailless) compared to control. Conclusion, semen quality decreases with consumed MSG for the long term. For this reason, reconsidering the use of MSG as an enhancer for the teste of food is very important.Keywords: epididymis, Monosodium L-Glutamate, semen quality.